Efficacy and safety of novel carbapenem-β-lactamase inhibitor combinations: imipenem-cilastatin/relebactam results from randomized controlled trials - Yang, Qingxin; Yang, Yanqiu; He, Rong; Yu, Bin; Zhong, Yueling; Lin, Fei (Frontiers in Medicine, 2023)
Background Gram-negative bacteria is a global public health problem. Treatment options include novel beta-lactamase inhibitors. Objectives The objective of this study was to collect information on the efficacy and safety of novel β-lactamase inhibitor combinations such as imipenem-cilastatin/relebactam (IMI/REL). Methods In order to comprehensively evaluate the clinical, microbiological, and adverse events outcomes, a meta-analysis was conducted on clinical trials comparing novel β-lactamase inhibitor combinations with existing comparator therapies. Results Four studies comprising 948 patients were included in the analysis. IMI/REL therapy demonstrated similar clinical responses to comparators across various treatment visits, including discontinuation of intravenously administered therapy visits [DCIV, RR = 1.00 (0.88, 1.12)], early follow-up visits [EFU, RR = 1.00 (0.89, 1.14)], late follow-up visits [LFU, RR = 1.00 (0.88, 1.13)]. Moreover, no significant difference in the microbiologic response of MITT patients was observed between IMI/REL and comparators across DCIV [RR = 0.99 (0.89, 1.11)], EFU [RR = 1.01 (0.95, 1.07)], and LFU visits [RR = 1.00 (90.94, 1.07)]. In terms of safety, therapy with IMI/REL and comparators exhibited similar risks of at least one adverse event (AE), drug-related AEs, and discontinuation due to AEs. The incidence of serious AEs (SAEs) was significantly lower in the IMI/REL group compared to the comparison groups. The predominant AEs were gastrointestinal disorders, with no significant difference observed between the IMI/REL group and comparators. Conclusion The clinical and microbiologic response to IMI/REL in the treatment of bacterial infection was comparable to that of the comparator. Furthermore, the incidence of AEs and the tolerability of IMI/REL were similar among the comparators. Based on these findings, IMI/REL can be considered as a viable alternative treatment option.